Online Learning Impacts on Academic Burnout: A Literature Review - Gita Aulia Nurani; Raissa Yulian Nafis; Afifah Nurfitria Ramadhani; Maharani Prastiwi; Naufal Hanif; Dio Ardianto (Journal of Digital Learning and Education, 2022)
Several reasons contribute to specific students' academic burnout due to the ongoing transformations in online learning. This literature review aims to determine how and to what extent students experienced burnout during the COVID-19 epidemic. Utilizing Google Scholar, 16 journals with the keyword "student's academic burnout" are uncovered through a study of the relevant literature. The analysis results of 15 journal papers indicate that students' learning processes induce academic burnout, so they exhibit emotional and physical tiredness, a tendency to depersonalize, and a lack of learning motivation. This has numerous effects on students, including rapid emotional change and heightened sensitivity. In addition, burnout has several adverse effects, including poor academic accomplishment, academic procrastination by students, decreased sleep quality, and suboptimal academic work, which calls for additional research to address academic burnout issues in students. This review concludes that most students during this epidemic reported burnout at medium to severe levels.